2020
DOI: 10.3390/plants9040486
|View full text |Cite
|
Sign up to set email alerts
|

AM-Induced Alteration in the Expression of Genes, Encoding Phosphorus Transporters and Enzymes of Carbohydrate Metabolism in Medicago lupulina

Abstract: Plant–microbe interactions, including those of arbuscular mycorrhiza (AM), have been investigated for a wide spectrum of model plants. The present study focuses on an analysis of gene expression that encodes phosphate and sugar transporters and carbohydrate metabolic enzymes in a new model plant, the highly mycotrophic Medicago lupulina MLS-1 line under conditions of phosphorus deficiency and inoculation with Rhizophagus irregularis. Expression profiles were detected by RT-PCR at six plant stages of developmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 72 publications
0
9
0
Order By: Relevance
“…This was preceded by the stage with high expression of the MtPT2 gene (above the expression level of the reference gene, actin). It should be assumed, at the beginning of stemming, plants without AM begin to experience significant phosphate starvation, which can be judged by the delay at the development stage and the lag in the dynamics of physiological parameters relative to the variant with AM [20]. Based on the fact that plants without AM are able to flower and bear fruit under such stressful conditions of low Pi, it can be supposed it is MtPT1 that plays an important role in the adaptation of plants without AM to conditions of low Pi levels in the soil.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This was preceded by the stage with high expression of the MtPT2 gene (above the expression level of the reference gene, actin). It should be assumed, at the beginning of stemming, plants without AM begin to experience significant phosphate starvation, which can be judged by the delay at the development stage and the lag in the dynamics of physiological parameters relative to the variant with AM [20]. Based on the fact that plants without AM are able to flower and bear fruit under such stressful conditions of low Pi, it can be supposed it is MtPT1 that plays an important role in the adaptation of plants without AM to conditions of low Pi levels in the soil.…”
Section: Discussionmentioning
confidence: 99%
“…cDNA synthesis was performed using the Maxima First Strand cDNA synthesis kit with dsDNase according to Thermo Scientific protocol from 1 μg total RNA for each sample. Real-time PCR for the following genes was performed using the presented primer sets: MlPT1 (PT1-2F "TACTCACTCACATTCTTCTTTGC" and PT1-2R "CCAAGCATGATAAGAGAGTTCTTA"; MN737457), MlPT2 (PT2-2F "CAGAACAAGGACAAGAGTAAAGC" and PT2-2R "CCGTTTTGTTATGAGAATGAGATTG"; MN737458), MlPTGC4 (PT4-1F "RGGGATTGA" "GGCCACACCGGTGACTAAG"; MN737459) and MlATP1 (ATP1-2F "CCTTTGTCATGGGTTATGGAAG" and ATP1-2R "CATTTTCCGTCGCGAAGTACC"; MN737456), MlActin (beta actin as a reference gene; actin7-f2 "GGCAGATGCTGAGGATATTCAA" and actin7-r2 "GTATGACGAGGTCGGCCAA"; MN756679) according to [20]. The level of gene expression was assessed using the BioRad CFX-96 thermocycler (BioRad, USA) and using the qPCR-RT reagent kit in the presence of SYBR Green I: +95°C, 10 min, 1 cycle; +95 °C, 15 sec, +60 °C, 30 sec, +72 °C, 30 sec, 40 cycles.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The transcriptomic analysis of the model PMS "Medicago lupulina + Rhizophagus irregularis", with MGR > 350% under conditions of phosphorus (P) deficiency for plant nutrition is promising [46]. The micro-vegetative experiments in M. lupulina provided in our earlier experiments during the development of AM symbiosis showed significant changes in the course of development and hormonal rearrangements in the host plant [47,48]; metabolic rearrangements [30,49]; and changes in the expression of a number of genes for carbohydrate metabolism and P transport [50].…”
Section: Introductionmentioning
confidence: 98%
“…On the plant side, the most common genes used are the AMF-induced phosphate transporter genes, e.g., PT4 in Medicago truncatula , Lycopersicon esculentum and Solanum tuberosum [ 11 , 21 , 22 ], and PT11 in Oryza sativa [ 23 ]. They are reliable plant molecular markers of a functional AMF symbiosis [ 24 ]. In a previous work on grapevine, we also demonstrated that the presence of many arbuscules in the cortex was associated with a high-level expression of two phosphate transporter genes (PHT1) in roots [ 4 ].…”
Section: Introductionmentioning
confidence: 99%